Glucose‐lowering effect of the DPP‐4 inhibitor sitagliptin after glucose and non‐glucose macronutrient ingestion in non‐diabetic subjects. Issue 6 (7th February 2013) - Ohlsson, L.; Alsalim, W.; Carr, R. D.; Tura, A.; Pacini, G.; Mari, A.; Ahrén, B.
Abstract Aim Recent studies suggest that the incretin concept is not restricted to glucose ingestion but relevant also after non‐glucose macronutrient administration. We therefore hypothesized that raising incretin hormones reduces circulating glucose after both glucose and non‐glucose macronutrient ingestion in healthy subjects. Methods Twelve healthy subjects received the dipeptidyl peptidase‐4 inhibitor sitagliptin (100 mg) or placebo before ingestion of glucose, fat (olive oil) or protein mix in equicaloric amounts (8 kcal/kg) plus paracetamol (1.5 g). The 120‐min areas under curve (AUC) of intact glucagon‐like peptide‐1 (GLP‐1), glucose, insulin, C‐peptide, glucagon and paracetamol, and model‐derived insulin secretion rate (ISR), insulin sensitivity, insulin clearance and glucose absorption were measured. Results The increased plasma intact GLP‐1 levels after each macronutrient was augmented by sitagliptin. This was associated with a robust lowering of glucose: glucose excursion after oral glucose was diminished, and glucose fell below baseline after oral fat and protein. In spite of lower glucose, AUCC‐peptide and ISR did not differ significantly between sitagliptin and placebo after any macronutrient. AUCglucagon, insulin sensitivity and insulin clearance were also not different between sitagliptin and placebo. Glucose absorption after oral glucose was reduced by sitagliptin, whereas AUCparacetamol was not statistically different between sitagliptin and placebo. Conclusions Physiological elevation of intact GLP‐1 levels after ingestion of glucose and non‐glucose macronutrients is robustly glucose‐lowering in healthy subjects. Hence, the incretin concept is not restricted to glucose ingestion in normal physiology. The glucose‐lowering action of sitagliptin at these low glucose levels in healthy subjects may have complex mechanisms, involving both islet‐dependent and islet‐independent mechanisms.